A retrospective observational study of clinicopathological features of KRAS, NRAS, BRAF and PIK3CA mutations in Japanese patients with metastatic colorectal cancer - Kawazoe, Akihito (BMC Cancer, 2015)
BACKGROUND: The mutation in KRAS exon 2 is a validated biomarker of resistance to anti-epidermal growth factor receptor (EGFR) therapy in metastatic colorectal cancer (mCRC). Several reports have confirmed associations of other RAS mutations with resistance to anti-EGFR therapy. However, the impact of BRAF and PIK3CA mutations on the efficacy of anti-EGFR therapy remains controversial. Little is known about the frequencies and clinicopathological features of these mutations, as well as the therapeutic effects of anti-EGFR therapy in mCRC patients with these mutations, especially in the Asian population. METHODS: In this retrospective observational study, frequencies and clinicopathological features of KRAS, NRAS, BRAF and PIK3CA mutations were evaluated in patients with mCRC. Among patients treated with anti-EGFR therapy, objective response, progression-free survival (PFS), and overall survival (OS) were evaluated according to gene status. RESULTS: Among 264 patients, mutations in KRAS exon 2, KRAS exons 3 or 4, NRAS, BRAF and PIK3CA were detected in 34.1%, 3.8%, 4.2%, 5.4% and 6.4%, respectively. Thus, a total of 12.1% of patients without KRAS exon 2 mutations had other RAS mutations. Primary rectal tumors tended to be more frequently observed in RAS mutant tumors. BRAF mutations were more frequently observed with right-sided colon, poorly differentiated or mucinous adenocarcinoma, and peritoneal metastasis. Among the 66 patients with KRAS exon 2 wild-type tumors treated with anti-EGFR agents, PFS (5.8 vs. 2.2 months) and OS (17.7 vs. 5.2 months) were significantly better in patients with all wild-type tumors (n = 56) than in those with any of the mutations (n = 10). The response rate also tended to be better with all wild-type tumors (26.8 vs. 0%). CONCLUSION: Other RAS and BRAF mutations were observed in KRAS exon 2 wild-type tumors, which were associated with some clinicopathological features and resistance to anti-EGFR therapy in our patient cohort. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-015-1276-z) contains supplementary material, which is available to authorized users.